Cystic Papillary Adenocarcinoma in Mammary Gland of a Wistar Rat – A Case Report - Venkatesan, P.S.; S.Sundaresan; S.Sowmiya; M.Eswarya; M.Madhavaselvi (The Indian Veterinary Journal, 2026)
A case of cystic papillary adenocarcinoma in an aged female Wistar rat on the posterior mammary glands is reported. A firm spherical mass approximately 2 cm in diameter was observed in the posterior pair of mammary glands, covered with skin. The rat was euthanized and a detailed necropsy examination was carried out. Representative tissue samples of the mass were collected in formalin, and histopathological examination revealed cystic papillary adenocarcinoma.